Pengaruh Metode Poster Comment Terhadap Kemampuan Menulis Deskripsi Siswa Kelas V SD Upt SDN No. 181 Pattopakang Kecamatan Mangarabombang Kabupaten Takalar - Nurhikmah Nurhikmah; Munirah Munirah; Tarman A Arif (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
The Effect of the Poster Comment Method on Learning Outcomes of Writing Description of Class V Students of UPT SDN No 181 Pattopakang, Mangarabombang District, Takalar Regency. A Thesis of Primary School Teacher Education Department, Faculty of Teacher Training and Education, Universitas Muhammadiyah Makassar. Supervised by Munirah Madeamin as the first supervisor and Tarman A Arif as the second supervisor.This research discusses about the effect of poster comment method on the Indonesian language writing learning outcomes of the 5th grade student of V UPT SDN No 181 Pattopakang District, Takalar Regency. This research used pre- experimental design. The research population consisted of students of V UPT SDN No 181 Pattopakang , Mangarabombang District, Takalar regency. The research used purposive sampling technique, while the samples in this research were the 5th grade students, which consisted of 21 students. The research instruments were; observation and test of learning outcomes.